Current Progress in Optimising Sustainable Energy Recovery From Cattle Paunch Contents, a Slaughterhouse Waste Product - Dowd, Bronwyn; McDonnell, Declan; Tuohy, Maria G. (Frontiers in Sustainable Food Systems, 2022)
Paunch contents are the recalcitrant, lignocellulose-rich, partially-digested feed present in the rumen of ruminant animals. Cattle forage in Europe is primarily from perennial and Italian ryegrasses and/or white clover, so paunch contents from forage-fed cattle in Europe is enriched in these feedstuffs. Globally, due to its underutilisation, the potential energy in cattle paunch contents annually represents an energy loss of 23,216,548,750 - 27,804,250,000 Megajoules (MJ) and financial loss of up to €800,000,000. Therefore, this review aims to describe progress made to-date in optimising sustainable energy recovery from paunch contents. Furthermore, analyses to determine the economic feasibility/potential of recovering sustainable energy from paunch contents was carried out. The primary method used to recover sustainable energy from paunch contents to-date has involved biomethane production through anaerobic digestion (AD). The major bottleneck in its utilisation through AD is its recalcitrance, resulting in build-up of fibrous material. Pre-treatments partially degrade the lignocellulose in lignocellulose-rich wastes, reducing their recalcitrance. Enzyme systems could be inexpensive and more environmentally compatible than conventional solvent pre-treatments. A potential source of enzyme systems is the rumen microbiome, whose efficiency in lignocellulose degradation is attracting significant research interest. Therefore, the application of rumen fluid (liquid derived from dewatering of paunch contents) to improve biomethane production from AD of lignocellulosic wastes is included in this review. Analysis of a study where rumen fluid was used to pre-treat paper sludge from a paper mill prior to AD for biomethane production suggested economic feasibility for CHP combustion, with potential savings of €11,000 annually. Meta-genomic studies of bacterial/archaeal populations have been carried out to understand their ruminal functions. However, despite their importance in degrading lignocellulose in nature, rumen fungi remain comparatively under-investigated. Further investigation of rumen microbes, their cultivation and their enzyme systems, and the role of rumen fluid in degrading lignocellulosic wastes, could provide efficient pre-treatments and co-digestion strategies to maximise biomethane yield from a range of lignocellulosic wastes. This review describes current progress in optimising sustainable energy recovery from paunch contents, and the potential of rumen fluid as a pre-treatment and co-substrate to recover sustainable energy from lignocellulosic wastes using AD.